Evaluation of CLSM measurements for dissolution studies – A case study investigating alumina dissolution in a silicate slag. Issue 19 (1st October 2022) - Harmuth, Harald; Burhanuddin,
Abstract: Several approaches to evaluate confocal laser scanning microscopy (CLSM) investigations for high-temperature dissolution studies with the aim of determining effective binary diffusivities are reviewed here. Limitations of the existing approaches render their application for accurate quantification of diffusion-controlled dissolution. Existing approaches are modified to correctly consider the contribution of the Stefan flow. A new approach that can account for fluid motion and bridge the gap to a stagnant flow is proposed. The new approach is compared with the existing approaches and their corresponding modifications. The new approach is also compared with rotating finger tests in the case of alumina dissolution in a silicate slag. The new approach shows a superior performance and agrees well with the finger test results.